Psychological empowerment and engagement in income generating activities among rural women in Yobe State, Nigeria - Musa, Zara Mallam (2017)
Psychological empowerment in this study refers to rural women’s experience of intrinsic motivation that is based on the cognitions in relation to their roles in income generating activities. There are four dimensions of psychological empowerment namely, meaningful, self-determination, competence and impact. Previous studies have shown a significant relationship between psychological empowerment and engagement. Nevertheless most of the previous literature did not consider the dimensions of psychological empowerment and engagement relationships especially in an informal setting. To bridge this gap, this study focused on examining the psychological empowerment and engagement in income generating activities among rural women in Yobe state, Nigeria. A model was developed based on self-determination theory, conservation of resources (COR) theory and previous studies. The objectives of this study are to examine the levels of psychological empowerment and engagement in income generating activities as well as to determine the extent to which psychological empowerment (meaningfulness, self-determination, competence, and impact) predicts engagement. In addition, the study also examined the moderating effect of family life stage on the relationship between psychological empowerment and engagement. A sample of 262 rural women were surveyed. Simple random sampling technique was used to select the sample consisting of participants of income generating activities in Damaturu, Yobe state, Nigeria. Data were gathered using of structured questionnaire adapted from previous studies. Both descriptive and inferential statistical analyses were conducted using SPSS (version 22.0) while Structural Equation Modeling (SEM-AMOS) was used to determine the moderating effect of family life stage on the relationship of psychological empowerment and engagement. The result from the descriptive analysis show that the rural women experience moderate level of psychological empowerment and high level of engagement in income generating activities. Additionally, the results from SEM indicates a significant contribution (42%) of psychological empowerment to engagement, and family life stage moderates the relationship between psychological empowerment and engagement. moreover, the result from SEM indicate that the standardized path coefficient were consistent with the hypothesis indicating a significant contribution of psychological empowerment to engagement based on the goodness-of-fit indices. Based on the results the researcher therefore concludes that all the four dimensions of psychological empowerment namely, meaningfulness, self-determination, competence and impact significantly contribute to rural women engagement in income generating activities, and family life stage moderates the relationship between psychological empowerment and engagement. The results support the use of self-determination theory and conservation of resources theory as theoretical foundation for the research model. Family life stage interacts with psychological empowerment to influence engagement. Thus, the results implies that the government should focus on the four dimensions so that women will be psychologically empowered and hence will be more engaged in their income generating activities. The Ministry of Women Affairs in charge of the program should enhance its policies on providing a child care support center for those with children and a flexible time for their involvement in income generating activities.